Geometrical Microfeature Cues for Directing Tubulogenesis of Endothelial Cells - Lei, Yifeng (Public Library of Science, 2012)
Angiogenesis, the formation of new blood vessels by sprouting from pre-existing ones, is critical for the establishment and maintenance of complex tissues. Angiogenesis is usually triggered by soluble growth factors such as VEGF. However, geometrical cues also play an important role in this process. Here we report the induction of angiogenesis solely by SVVYGLR peptide micropatterning on polymer surfaces. SVVYGLR peptide stripes were micropatterned onto polymer surfaces by photolithography to study their effects on endothelial cell (EC) behavior. Our results showed that the EC behaviors (cell spreading, orientation and migration) were significantly more guided and regulated on narrower SVVYGLR micropatterns (10 and 50 µm) than on larger stripes (100 µm). Also, EC morphogenesis into tube formation was switched on onto the smaller patterns. We illustrated that the central lumen of tubular structures can be formed by only one-to-four cells due to geometrical constraints on the micropatterns which mediated cell-substrate adhesion and generated a correct maturation of adherens junctions. In addition, sprouting of ECs and vascular networks were also induced by geometrical cues on surfaces micropatterned with SVVYGLR peptides. These micropatterned surfaces provide opportunities for mimicking angiogenesis by peptide modification instead of exogenous growth factors. The organization of ECs into tubular structures and the induction of sprouting angiogenesis are important towards the fabrication of vascularized tissues, and this work has great potential applications in tissue engineering and tissue regeneration.